Total and regional body composition of NCAA collegiate female rowing athletes - Juckett, W. T.; Stanforth, P. R.; Czeck, M. A.; Evanoff, N. G.; Dengel, D. R. (International Journal of Sports Medicine, 2023)
This study explored body composition in female NCAA Division I rowers compared to controls; and the effect of season, boat category, and oar side on body composition. This retrospective analysis of 91 rowers, and 173 age, sex, and BMI-matched controls examined total and regional fat mass (FM), lean mass (LM), bone mineral content (BMC), bone mineral density (BMD), percent body fat (%BF), and visceral adipose tissue (VAT) measured using dual X-ray absorptiometry. Two-sample t-testing was used to assess differences between rowers and controls. Repeated measures ANOVA analyzed differences across seasons. ANOVA analyzed differences between boat categories. Paired t-testing analyzed oar side versus non-oar side. Rowers had greater height (174.2; 164.1 cm), weight (75.2; 62.6 kg), LM (51.97; 41.12 kg), FM (20.74; 19.34 kg), BMC (2.82; 2.37 kg), and BMD (1.24; 1.14 g/cm2); but lower %BF (30.5%; 27.1%), and VAT (168.1; 105.0 g) than controls (p<0.05). Total, arm, and trunk muscle-to-bone ratio were greater in rowers (p<0.001). Rowers demonstrated greater arm LM (5.8 kg; 5.6 kg) and BMC (0.37 kg; 0.36 kg) in Spring compared to Fall (p<0.05). 1V8 rowers had a lower %BF than non-scoring rowers (25.7%; 29.0%; p=0.025). No differences observed between oar sides. These findings will help rowing personnel better understand body composition of female collegiate rowers.